H Historiografi Politik-Sosial Pendidikan Islam di Minangkabau: Transmisi Ilmu dan Konsep Talaqqī dalam Pembentukan Tradisi Keilmuan - Hayat, Ade Putra; Iswantir, Iswantir (STIT Ahlussunnah Bukittinggi, 2025)
This study examines the political-social historiography of Islamic education in Minangkabau, focusing on the transmission of knowledge and the concept of talaqqī in the formation of the Islamic scholarly tradition in the Indonesian archipelago. The study aims to trace, reconstruct, and interpret the historical dynamics of Islamic education in Minangkabau within the context of socio-politics and the transmission of knowledge. This study adopts a qualitative approach with historiography and literature review. Through a historical-critical literature review approach, this study analyzes the dynamics of Islamic education from the 17th to the 20th century, starting from the traditional surau system to modern madrasahs such as Sumatera Thawalib and Diniyah School. The results of the study show that Islamic education in Minangkabau not only functions as a religious institution but also as a socio-political arena in shaping the intellectual awareness and Islamic identity of the community. The concept of talaqqī becomes the epistemological foundation of knowledge transmission, which guarantees the authority and blessings of knowledge through the spiritual relationship between teacher and student. In the modern context, talaqqī has been recontextualized into a system of values and scientific ethics that is relevant to the development of contemporary Islamic education. This study confirms that Islamic education in Minangkabau is a manifestation of the dialectic between tradition and modernity, as well as an integrative model of Islamic education based on sanad, spirituality, and rationality.